Assessment of Clinical Skills and Knowledge in Ophthalmology in Undergraduate Medical Students - Amna Rizwan; Muhammad Ali; Nida Khalid; Asfandyar Asghar (Journal of University College of Medicine and Dentistry)
Objective: To evaluate the self-perceived competence and exposure of undergraduate medical students to clinical skills and theoretical knowledge in ophthalmology.